SiC Measurements of Electron Energy by fs Laser Irradiation of Thin Foils - Lorenzo Torrisi; Mariapompea Cutroneo; Alfio Torrisi (Micromachines, 2023)
SiC detectors based on a Schottky junction represent useful devices to characterize fast laser-generated plasmas. High-intensity fs lasers have been used to irradiate thin foils and to characterize the produced accelerated electrons and ions in the target normal sheath acceleration (TNSA) regime, detecting their emission in the forward direction and at different angles with respect to the normal to the target surface. The electrons’ energies have been measured using relativistic relationships applied to their velocity measured by SiC detectors in the time-of-flight (TOF) approach. In view of their high energy resolution, high energy gap, low leakage current, and high response velocity, SiC detectors reveal UV and X-rays, electrons, and ions emitted from the generated laser plasma. The electron and ion emissions can be characterized by energy through the measure of the particle velocities with a limitation at electron relativistic energies since they proceed at a velocity near that of the speed of light and overlap the plasma photon detection. The crucial discrimination between electrons and protons, which are the fastest ions emitted from the plasma, can be well resolved using SiC diodes. Such detectors enable the monitoring of the high ion acceleration obtained using high laser contrast and the absence of ion acceleration using low laser contrast, as presented and discussed.